Enhancing Satisfaction: A Quantitative Investigation Trought User Experience in Website Quality for Low Vision Disabled Students - Rahmah, Yusriyah; Aknuranda, Ismiarta; Ratnawati, Dian Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The background to this research problem stems from the need to understand the impact of service quality, user experience, and user satisfaction in website design for students with low vision disabilities who are taking part in the final assignment guidance process at Brawijaya University. Students with low vision disabilities often experience obstacles in the accessibility and use of information technology. Considering the important role of websites in academic contexts, a proper design must meet their needs. Therefore, this study investigates the relationship between service quality, user experience, and user satisfaction in website design for low vision disabled students during final assignment guidance at Brawijaya University. It aims to determine if enhancing service quality positively affects user experience and satisfaction, while also examining the mediating role of user experience. Data is gathered from 31 respondents, including low vision disabled students and relevant academics from the Disability Service Center, through questionnaires. Participants rate service quality, user experience, and satisfaction using predefined scales, and statistical analyses, including path analysis, are conducted to assess the relationships. Next, a regression test was carried out as the main statistical procedure to analyze the relationship between the variables involved in this research. The results of the regression analysis show that service quality has a positive and significant effect on user experience (β = 0.435, Sig = 0.000) and user satisfaction (β = 0.493, Sig = 0.003). User experience also has a positive and significant impact on user satisfaction (β = 0.397, Sig = 0.001). These findings indicate that improving service quality and user experience has the potential to increase user satisfaction. This research provides valuable insights into service quality, user experience, and satisfaction dynamics in website design for low vision disabled students, emphasizing the importance of prioritizing user experience to boost satisfaction, particularly within disability populations. Practical implications include improving website accessibility and academic support for low vision disabled students, with recommendations for staff training and student involvement in website development. Limitations include sample size constraints and potential lack of generalizability, suggesting the need for future research incorporating qualitative methodologies.